Artistic Cartography and Design Explorations Towards the Pluriverse - Miettinen, Satu (Routledge advances in art and visual studies, 2022)
"This edited volume uses an interdisciplinary approach to art and design that not only reframes but also repositions agendas and actions to address fragmented global systems. Contributors explore the pluriverse of art and design through epistemological and methodological considerations. What kinds of sustainable ways are there for knowledge transfer, supporting plural agendas, finding novel ways for unsettling conversations, unlearning and learning and challenging power structures with marginalised groups and contexts through art and design? The main themes of the book are art and design methods, epistemologies and practices that provide critical, interdisciplinary, pluriversal and decolonial considerations. The book challenges the domination of the white logic of art and design and shifts away from the Anglo-European one-world system towards the pluriverse. The book will be of interest to scholars working in art history, visual studies, arts-based research, and design studies"-- Provided by publisher.
Keywords: Art and society; Design : Social aspects; Cultural pluralism